Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1523-1747.1998.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Barrier Perturbation Abolishes the Ca2+ and K+ Gradients in Murine Epidermis: Quantitative Measurement Using PIXE

Abstract: Epidermal permeability barrier homeostasis requires the delivery of lipids and hydrolytic enzymes by lamellar body exocytosis from the uppermost granular cells, a process that is upregulated following barrier disruption. As lamellar body secretion is controlled by ionic concentrations, especially Ca2+ and K+, we used a quantitative technique, microbeam proton-induced X-ray emission, to measure Ca2+, K+, Cl-, and P concentrations before and after acute barrier perturbation by acetone applications. We found a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
153
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(170 citation statements)
references
References 24 publications
(40 reference statements)
12
153
0
Order By: Relevance
“…Previous studies by our and other laboratories have demonstrated that disruption of the permeability barrier results in a decrease in calcium and other ions in the outer Ϫ/Ϫ mice 3 hours after tape stripping (E) (n ϭ 5). Scale bars ϭ 10 m. nucleated layers of the epidermis, 10,49 modifying the distinctive calcium gradient of the epidermis 50 -54 and stimulating lamellar body secretion. Yet, although decreases in calcium stimulate lamellar body secretion, they simultaneously inhibit epidermal differentiation 52 ; hence, we suspect that a decrease in calcium in the outer epidermis would not stimulate terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our and other laboratories have demonstrated that disruption of the permeability barrier results in a decrease in calcium and other ions in the outer Ϫ/Ϫ mice 3 hours after tape stripping (E) (n ϭ 5). Scale bars ϭ 10 m. nucleated layers of the epidermis, 10,49 modifying the distinctive calcium gradient of the epidermis 50 -54 and stimulating lamellar body secretion. Yet, although decreases in calcium stimulate lamellar body secretion, they simultaneously inhibit epidermal differentiation 52 ; hence, we suspect that a decrease in calcium in the outer epidermis would not stimulate terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a steep calcium gradient within the oral mucosa, with higher calcium present in the uppermost differentiated layers, and altering extracellular calcium has been used to effectively model keratinocyte differentiation in vitro (13)(14)(15)(16). Immunohistochemical analysis of human keratinocytes indicates a correlation between MMP-9 expression and differentiation.…”
mentioning
confidence: 99%
“…Two enzymes essential for this processing, ␤-GlcCer'ase and acidic sphingomyelinase, require acidic milieu for optimal activity, 29,45 suggesting that epidermal permeability barrier homeostasis is dependent on SC pH. 46,47 When exposed to alkaline or neutral solutions, skin exhibits greater susceptibility to develop irritant/allergic contact dermatitis. 46 -48 A number of exogenous and intrinsic mechanisms have been proposed to contribute to SC acidity.…”
Section: Discussionmentioning
confidence: 99%